Implementation of SISKEUDES and the Dynamics of Village Financial Governance: A Case Study in Barru Subdistrict Barru Regency - M, A. Pananrangi (LPPPIPublishing, 2026)
Transparent and accountable village financial management is a fundamental prerequisite for achieving good village governance. To support this objective, the government has developed the Village Financial System Application (SISKEUDES) as a digital instrument to improve the quality of village financial administration and accountability.This study aims to analyze the implementation of SISKEUDES and the dynamics of village financial governance in Barru Subdistrict, Barru Regency, as well as to explore the adaptive strategies employed by village officials in addressing technical limitations and human resource capacity constraints. The research adopts a qualitative approach using a case study method conducted in five villages: Saiawung, Palakka, Tompo, Galung, and Anabanua. The informants consisted of 17 participants, including village heads, village treasurers, and SISKEUDES operators. Data were collected through in-depth interviews, direct observation, and documentation of financial reports and Village Revenue and Expenditure Budgets (APBDes).The findings indicate that SISKEUDES plays a significant role in improving administrative orderliness, reporting accuracy, and the ease of village financial supervision. The effectiveness of the system is influenced by the capacity of village officials, the intensity of technical assistance, and their ability to adapt to infrastructure constraints. The novelty of this study lies in revealing local adaptive practices among village officials, demonstrating that successful village financial governance emerges from a dynamic interaction between technology, human resources, and local contextual conditions.